Joint IRS and precoder design for OFDM-based mmWave massive MIMO systems - Ibwe, Kwame (Telecommunication systems, 2025)
This paper investigates the joint design of hybrid precoding and intelligent reflecting surface (IRS) phase shifts for wideband millimeter-wave (mmWave) massive MIMO systems. The design problem is formulated as a spectral efficiency maximization under hardware constraints, and a hybrid precoding with IRS design (HPID) algorithm is developed. The digital precoders are updated via projected gradient ascent with power projection, while the IRS phases are optimized using alternating optimization. A theoretical upper bound based on fully digital precoding is also derived for benchmarking. Simulation results show that the proposed scheme achieves over 20% higher spectral efficiency compared to conventional hybrid baselines and attains more than 90% of the fully digital upper bound. The algorithm converges within 15–20 iterations and maintains robust performance under phase noise, suitable candidate for high-throughput and reliable 6G wideband deployments.